Technology-enhanced mathematics instruction: A second-order meta-analysis of 30 years of research - Young, Jamaal (Educational research review, 2017)
It is important to assess the cumulative effects of technology on student achievement captured in the last 30 years of technologyenhanced mathematics instruction. Synthesizing the thousands of articles and gray literature on this subject is necessary but would require a considerable commitment of academic resources. A second-order metaanalysis or meta-analysis of meta-analyses is an alternative that is reasonable and effective. Thus, a second-order meta-analysis of 19 prior meta-analyses with minimum overlap between primary studies was conducted. The results represent 663 primary studies (approximately 141,733 participants) and 1,263 effect sizes. The random effects' mean effect size of .38 was statistically significantly different from zero. The results provide a historical and contextualized summary of 30 years of meta-analytic research, which supports meta-analytic thinking and better interpretation of future effect sizes. Results indicate that technology function and study quality are major contributors to effect size variation. Specifically, computation enhancement technologies were most effective, while studies that examine combinations of enhancements were least effective. Implications for technology-enhanced mathematics instruction and meta-analytic research are provided. •A second-order meta-analysis of technology-enhanced mathematics research is presented.•The mean effect size for this second order meta-analysis was g = 0.38.•Results suggest that technology didactical functionality should inform classroom use.•Researchers should examine meta-analytic study quality to improve effectiveness.•Results provide effect size benchmarks to contextualize future investigations.